Nutritive Value of Azolla as Poultry Feed-A Review - Swain, Bijaya Kumar; Naik, Prafulla Kumar; Beura, Chandrakant (Indian Journal of Animal Nutrition, 2022)
Azolla has great prospective as poultry feed due to its high content of proteins, essential amino acids, vitamins (vitamin A, vitamin B12, β-Carotene), growth promoter intermediaries and minerals. It has higher  potential to proliferate without inorganic nitrogen fertilization and   high rate of growth in water. Azolla on meal basis can be included in broiler ration and pullet chick ration up to a level of 5 and 10% , respectively without any adverse effect on their performance. Fresh azolla at a rate 200g/duck/day in White Pekin duck feeding was economical. Higher levels of inclusion of azolla limit its beneficial effect due to decrease in feed consumption owing to higher level of fibre comprising mostly of ADF and lignin in azolla.